2002
DOI: 10.1128/aac.46.11.3634-3636.2002
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Pharmacodynamic Properties of Three Antifungal Agents against PreformedCandida albicansBiofilms Determined by Time-Kill Studies

Abstract: We have examined the in vitro activities of fluconazole, amphotericin B, and caspofungin against Candida albicans biofilms by time-kill methodology. Fluconazole was ineffective against biofilms. Killing of biofilm cells was suboptimal at therapeutic concentrations of amphotericin B. Caspofungin displayed the most effective pharmacokinetic properties, with >99% killing at physiological concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
154
2
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 228 publications
(165 citation statements)
references
References 15 publications
7
154
2
2
Order By: Relevance
“…The development and characterization of Candida biofilms on bioprosthetic surfaces that are components of indwelling devices are well documented (5,13,14,23). These studies have shown that Candida biofilm development is closely associated with the generation of an extracellular matrix and that mature biofilms show a highly heterogeneous structure and grow variably depending on the topography of the substrate.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The development and characterization of Candida biofilms on bioprosthetic surfaces that are components of indwelling devices are well documented (5,13,14,23). These studies have shown that Candida biofilm development is closely associated with the generation of an extracellular matrix and that mature biofilms show a highly heterogeneous structure and grow variably depending on the topography of the substrate.…”
Section: Discussionmentioning
confidence: 95%
“…It is now recognized that antibiotic resistance is a general trait associated with biofilm organisms, including bacteria (21,22) and fungi (15,23). Several theories have been proposed to explain this phenomenon, including the growth rate differen- tials (9, 10), a recalcitrant phenotypic state (4), the production of antibiotic-degrading enzymes (11), and the extracellular polymeric material that may act as an adsorbent or a reactant with the antimicrobial (30).…”
Section: Discussionmentioning
confidence: 99%
“…Overall this microtiter platebased model of biofilm formation offers a simple, flexible, relatively inexpensive, accurate and reproducible alternative for biofilm formation that is compatible with the widely available 96 well microplate platform. It can be used to examine multiple parameters and factors influencing biofilm formation, to estimate the biofilm-forming ability of multiple fungal isolates and mutant strains, and more importantly for the purpose of these studies, it can be easily adapted for antifungal susceptibility testing of fungal biofilms following the procedures described below 25,31,32 .…”
Section: Introductionmentioning
confidence: 99%
“…93 Researchers have observed that 20 times the MIC of commonly used antifungals was required to achieve a significant reduction in cell numbers. 94 Thus, higher levels of AmB-D are required to manage biofilm-related infection in the clinic, and this is not advisable because of the toxic behavior of AmB.…”
Section: Regression Of C Albicans Biofilm Induced By Amb-pgamentioning
confidence: 99%